CLASSIFICATION OF FURNITURE AND DECORATIVE FABRICS - OLIJNYK, HALINA; KORNYTSKA, LARYSA; DANCHENKO, YULIYA; RASTORHUIEVA, MARIIA; YEVTUSHENKO, VALENTYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
One of the promising and dynamic segments of the light industry market in Ukraine and Europe is the market of furniture and decorative materials for modern interiors. The production of furniture and decorative fabrics is dynamically developing all over the world and is the most knowledge-intensive and multi-vector. The domestic and global market of furniture and decorative fabrics demonstrates considerable stability due to the wide range of demand and variety of this product. The need for different production methods, hygienic and aesthetic furniture, decorative fabrics, and a significant expansion and optimization of the assortment pose the task of providing information to consumers of the domestic market. The importance of furniture and decorative materials in the modern interior is difficult to overestimate since the areas of their application are constantly updated and improved. Recently, there has been a tendency to increase the capacity of furniture and decorative fabrics in the market of Ukraine. According to the results of literary research, the volume of consumption of furniture and decorative fabrics from the beginning of the XXI century. increased by 50%. However, such growth is ensured not by a significant increase in the volume of domestic production, but at the expense of imports. A characteristic feature of the Ukrainian market of furniture and decorative fabrics nowadays is a too great advantage of imported goods over similar goods of domestic production. Today, there is such a situation that the rate of growth of domestic production of furniture and decorative fabrics in Ukraine is significantly inferior to the rate of import growth. Ukraine’s light industry is in a state of protracted systemic crisis: business ties with traditional suppliers of raw materials have been destroyed, and production of equipment for the light industry has practically stopped. In Ukraine, there are no state-owned enterprises for the production of furniture and decorative fabrics, they are produced only at private enterprises. At the same time, there is no consensus in the textile industry regarding the creation and organization of the classification of furniture and decorative fabrics. That is why, for the further development of the production of furniture and decorative fabrics, a more indepth study of their properties, and the unification of work on the quality assessment of this product, it is important to have a clear classification of it. Currently, in Ukraine, the classification of furniture and decorative fabrics is carried out in accordance with the Ukrainian Classification of Goods of Foreign Economic Activity (UKTZED). Since there is currently no information and analytical center for the light industry in Ukraine, there is no extensive statistical accounting of production volumes and other economic indicators of enterprises, and the presence of a clear classification of fabrics according to certain characteristics will limit access to the domestic market of potentially dangerous products. That is why further scientific research is aimed at creating a classification system for furniture and decorative fabrics. The purpose of the classification of furniture and decorative fabrics is to study the origin of the raw materials from which they are made, the method of production, and the functional purpose of the products obtained on their basis. According to the results of scientific research, the object of classification - furniture - decorative fabrics is proposed to be divided according to the following classification features: raw material (class), origin (group, subgroup), production method (genus), and product purpose (functional purpose). When developing the system of classification of furniture and decorative fabrics, all methodical rules of its construction were taken into account. The compilation of such a scheme was based on the application of a hierarchical method of classification, which made it possible to display high informativeness, capacity, and logical sequence. In this classification system, it is proposed to divide the totality of furniture and decorative fabric products according to the classification feature "origin". Its name reflects the method of obtaining and predicts the scope of further industrial application. The classification of furniture and decorative fabrics proposed by the authors can complete and improve the informative market, and eliminate technological and marketing barriers in the production, sale, and consumption of finished products.